Mindfulness Based Cognitive Therapy Untuk Meningkatkan Konsep Diri Remaja Post-Traumatic Stress Disorder - Firsty Ajeng Wulandari; Indria Laksmi Gamayanti (Universitas Islam Indonesia, 2014)
This research aims in identified the effectiveness of mindfulness based cognitive therapy as an alternative to promoted the self-concept on adolescent with burn injury and post-traumatic stress disorder after Merapi eruption of 2010. The number of the research subject was one adolescent aged 17 years old suffered from combustio grade II – III, with the distribution of the burn injury was 38 % resulted in physical disability, and PTSD after Merapi eruption of 2010. The data collection was conducted using observation, interview and scale. This research was single case experimental design research with the research design n=1 and the measurement design AB–Follow up. The analysis of the collected data involved the measurement using two methods, namely: (1) Visual inspection technique which represented the graphic based on the result score of PTSD and self-concept scales on the stages of baseline, intervention, and follow up which was then analyzed; (2) Qualitative analysis method usedin-depth interview and observation during the stages of assessment, baseline, intervention, and follow up. The results of this study indicated that there was an increase in self-concept was seen in the form of the internal dimensions of identity as the person and valuer, and external dimensions of self-concept in the form of physical, personal, social, moral, ethical, family, academic. There was also a significant decrease in PTSD based on the DSM IV.Keywords: Mindfulness Based Cognitive Therapy, Self Concept, Post-Traumatic Stress Disorder